1992
DOI: 10.3109/10242429209014897
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Heterogeneity of aCandida cylindracea(rugosa) Lipase: Monitoring of Esterolytic Activity and Enantioselectivity by Chiral Liquid Chromatography

Abstract: A method for the determination of lipase activity in terms of rate and enantioselectivity of hydrolysis of a chiral ester substrate has been developed. When this method was applied to fractions, isolated from preparative, column chromatographic separations (anion-exchange, molecular sieve) of the lipase, significant differences in enantioselectivity (E) was found between the fractions. The highest enantioselectivity was found in the first main peak obtained on DEAE-Sepharose chromatography, meaning that the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These isoenzymes and/or isoforms have different activities and stereospecificities for many fine chemical synthesis reactions 7. 13, 14 The enantiomeric ratio ( E ) of pure CRL isoenzymes in the hydrolysis of Naproxen methyl ester was 186 for CRL A and 60 for CRLB 15. It has been speculated that enhanced enantioselectivity in repeated batch reactions might be related to mutual transformation of CRL isoenzymes during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…These isoenzymes and/or isoforms have different activities and stereospecificities for many fine chemical synthesis reactions 7. 13, 14 The enantiomeric ratio ( E ) of pure CRL isoenzymes in the hydrolysis of Naproxen methyl ester was 186 for CRL A and 60 for CRLB 15. It has been speculated that enhanced enantioselectivity in repeated batch reactions might be related to mutual transformation of CRL isoenzymes during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Many lipases have shown their enantioselectivity for the hydrolysis of esters or synthesis of esters from acids and alcohols (Allenmark and Ohlsson, 1992;Russel and Klibanov, 1988;Weissfloch and Kazlauskas, 1995;Wen et al, 1996). Our previous paper (Kwon, 1992) showed that some lipases had a high enantioselectivity for synthesis of esters.…”
Section: Introductionmentioning
confidence: 99%